2020
DOI: 10.1002/ijgo.13104
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐Müllerian hormone as a marker of abortion in the first trimester of spontaneous pregnancy

Abstract: Objective To assess anti‐Müllerian hormone (AMH) levels as a marker of early abortion in the first trimester among women younger than 35 years. Methods Prospective study of women aged 18–34 years with a spontaneous pregnancy at less than 12.6 gestational weeks in Łódź, Poland, between January 2017 and November 2018. Cases of anembryonic abortion and assisted conception were excluded. Blood samples were collected and assayed for serum AMH levels. Data were compared between women with an embryo with no cardiac a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Similar to our study, Kostrzewa et al [ 27 ] reported that in patients younger than 35 years with a spontaneous pregnancy, both low (< 1.1 ng/mL) and high (> 4.5 ng/mL) AMH concentrations significantly increased the risk of pregnancy loss in the first trimester. Gleicher et al [ 28 ] built logistic regression models to predict IVF outcomes.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar to our study, Kostrzewa et al [ 27 ] reported that in patients younger than 35 years with a spontaneous pregnancy, both low (< 1.1 ng/mL) and high (> 4.5 ng/mL) AMH concentrations significantly increased the risk of pregnancy loss in the first trimester. Gleicher et al [ 28 ] built logistic regression models to predict IVF outcomes.…”
Section: Discussionsupporting
confidence: 91%
“…The rates of pregnancy loss are higher among women with PCOS than among women without the syndrome [ 32 , 33 ]. The abovementioned studies also showed similar pregnancy outcomes among women without PCOS but with high AMH levels [ 27 – 29 ]. Nilsson et al [ 34 ] reported that AMH suppresses growth differentiation factor 9 (GDF9) and bone morphogenetic protein 15 (BMP15) expression.…”
Section: Discussionmentioning
confidence: 86%
“…In contrast, the adjusted relative risk of miscarriage corresponding to AMH levels <1.0, 1.0–3.5 versus >3.5 ng/mL was 1.13 (0.74–1.72) versus Ref versus 1.13 (0.82–1.56) in another prospective study 22 . Kostrzewa et al reported RR for miscarriage corresponding AMH levels <1.1 versus 1.1–4.5 versus >4.5 ng/mL was 3.66 (2.1–6.4, p < 0.001) versus Ref versus 3.0 (1.61–5.59, p < 0.001), although the study recruited only 66 women 19 . Based on the conflicting results and inconsistent study designs, the systematic review concluded that clinical recommendations could not be offered 18 …”
Section: Resultsmentioning
confidence: 97%
“…22 Kostrzewa et al reported RR for miscarriage corresponding AMH levels <1.1 versus 1.1-4.5 versus >4.5 ng/mL was 3.66 (2.1-6.4, p < 0.001) versus Ref versus 3.0 (1.61-5.59, p < 0.001), although the study recruited only 66 women. 19 Based on the conflicting results and inconsistent study designs, the systematic review concluded that clinical recommendations could not be offered. 18 CQ2.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, research found that high levels of serum AMH had a significantly higher risk of miscarriage in women with or without PCOS [ 46 ]. Similarly, an increased rate of miscarriage has been reported in women with high or low AMH levels [ 47 ]. High serum AMH levels were also associated with an increased risk of preterm delivery in women with PCOS [ 48 ].…”
Section: Discussionmentioning
confidence: 95%